Epidemiology of Glomerular Disease in Southern Arizona: Review of 10-Year Renal Biopsy Data. Issue 18 (May 2016) - Murugapandian, Sangeetha; Mansour, Iyad; Hudeeb, Mohammad; Hamed, Khaled; Hammode, Emad; Bijin, Babitha; Daheshpour, Sepehr; Thajudeen, Bijin; Kadambi, Pradeep
Abstract : Abstract: Glomerulonephritis stands third in terms of the etiologies for end-stage kidney disease in the USA. The aim of this study was to look at the patterns of biopsy-proven glomerulonephritis based on data from a single center. Kidney biopsy specimens of all patients above the age of 18 years, over a 10-year period, who had diagnosis of nondiabetic glomerular disease, were selected for the study. The most common histopathological diagnosis was focal and segmental glomerulosclerosis (FSGS) (22.25%, 158/710) followed by membranous nephropathy (20.28%, 144/710) and immunoglobulin (Ig)A nephropathy (19.71%, 140/710). There was male preponderance in all histological variants except IgA nephropathy, lupus nephritis, and pauci-immune glomerulonephritis. The race distribution was uneven, and all histological variants, except minimal change disease and lupus nephritis, were more commonly seen in whites. In a separate analysis of the histological pattern in Hispanics, lupus nephritis was the most common pathology (28.70%, 62/216) followed by FSGS (18.05%, 39/216). In American Indian population, the most common pathology was IgA nephropathy (33.33%, 8/24) followed by FSGS (16.67%, 4/24). This study highlights the histopathological patterns of glomerular disease in southern Arizona. The data suggest regional and ethnic variations in glomerular disease that may point towards genetic or environmental influence in the pathogenesis of glomerular diseases.